Pengaruh Kualitas Produk Dan Brand Trust Terhadap Keputusan Pembelian Smartphone Samsung (Studi Mahasiswa Pengguna Smartphone Samsung di Unisma) - Erminawati, Erminawati; Nurhidayah, Nurhidayah; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The large growth of smartphones in Indonesia certainly causes competition with each other, for example, Samsung brand smartphones have used various methods to maintain their existence and increase the number of sales each period. In winning competition in the business world, the thing that becomes a company's competitive advantage is the purchasing decisions of its consumers. Understanding consumer purchasing decisions is not easy because purchasing decisions are influenced by various factors such as product quality and brand trust. In this research, a quantitative approach is used, where this research has conducted tests on Unisma students who use Samsung smartphones in the city of Malang. The results of this research can prove that there is a positive influence between product quality and brand trust variables on Samsung smartphone purchasing decisions. The conclusions drawn are only based on quantitative data analysis, so it is hoped that there will be further research regarding product quality and brand trust on decisions. purchasing different research methods or qualitative methods, wider samples, and the use of different and more complete research instruments. Keywords: product quality, brand trust, on purchasing decision.